Comparison of ease of endotracheal intubation with fixed height pillow versus pillow height attained by alignment of external auditory meatus to sternal notch - Priyanka Bansal; Pulkita Kataria; Kirti Kshetrapal; Hemant Kamal; Renu Bala; Geeta Ahlawat (Asian Journal of Medical Sciences, 2024)
Background: Endotracheal intubation is considered to be the “Gold Standard” for airway management during the administration of general anesthesia and in critical care setting because of its advantages, which allows delivery of anesthetic gases and oxygen through positive pressure ventilation without inflation of stomach, permits access to tracheobronchial tree for pulmonary hence minimizing the risk of gastric content aspiration, and improves surgical access to head and neck. The major determinants of easy tracheal intubation are optimal laryngoscopy and a good visualization of the glottis.